Eksistensi Fiqih Wali Mujbir Syafi’i Ditinjau dari UU No.12 Tahun 2022 tentang Kejahatan Kekerasan Seksual - Wafa, Zaein; Azmi, Miftahudin (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2024)
Forced marriage by guardians is recorded as a form of sexual violencein Indonesia. Government regulation Article 10 of Law No. 12 of 2022explains that forced marriage is divided into 3, namely child marriage, inthe name of culture, and rape victims. The background of this research isdue to the problem of the great authority held by the guardian of the mujbiras the guardian of the marriage of children or grandchildren. This greatauthority is in the form of forced marriage carried out by the guardian ofthe mujbir without the consent of the bride. The concept of the guardian ofthe mujbir is a concept contained in the views of the Imam Syafi’i schoolof thought, as one of the schools of thought widely used in Indonesia. Thepractice of the guardian of the mujbir in Indonesia certainly raises problemswhen associated with the provisions of Article 10 of Law Number 12 of2022, which states that forced marriage is a criminal act of sexual violence.So there are two legal problems. First, is it possible for the view of theImam Syafi’i school of thought on wali mujbir to be applied in Indonesiasecond, how is the legitimacy of the authority to force marriage held by thewali mujbir reviewed from the objectives of Islamic law maqashid shariaBy using the normative legal research method with a conceptual approachand literature study method, the results obtained are that the concept ofwali mujbir is contrary to Law Number 12 of 2022 because it causes forcedmarriage which is a criminal act of sexual violence so that the view onthe concept of wali mujbir cannot be implemented in Indonesia. Viewedfrom the perspective of its benefits, the concept of wali mujbir is not morebeneficial. It causes more forced marriage practices and does not protectwomen and their rights.